THE ROLE OF PROVISION WITH IODINE IN FORMING OF INTELLECTUAL AND SOMATIC HEALTH IN CHILDREN - O.V. Stennikova; A.E. Boborykina; L.V. Levchuk ("Paediatrician" Publishers LLC, 2009)
This article presents the data on iodine physiological role, the prevalence and the reasons of iodine deficiency among children in Russian Federation. Authors describe negative influence of iodine deficiency on somatic health, cognitive functions and fine motor coordination forming in children of different age, indices of linear growth and harmonicity of physical development. The data on Russian and foreign trials studying modern methods of prophylaxis of iodine deficiency, was presented.Key words: children, iodine, deficiency, prophylaxis.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):48-53)